Achieving sustainable food security for all: required policy action - Pinstrup-Andersen, Per (Wageningen University & Research, 2001)
With business as usual, neither the World Food Summit Goal nor the 2020 Vision will be achieved. The lecture identifies the key driving forces that will influence the prospects for sustainable food security in coming years and proposes a set of high priority policy actions. Both the World Food Summit Goal and the 2020 Vision can be achieved but only if appropriate policies are followed within a three-pronged approach: Pro-poor economic growth, Empowerment of the poor, and Effective provision of public goods.